2020
DOI: 10.1111/cts.12864
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Mesenchymal Stem Cells for Postmastectomy Lymphedema: A Literature Review

Abstract: Upper limb lymphedema is one of the most common complications after breast cancer surgery and radiotherapy. Despite various physical therapy and surgical options available, the impaired lymph fluid drainage may be progressive due to lymphatic vascular insufficiency making treatment more difficulty. Stem cell therapy provides a promising alternative in the treatment of various chronic diseases. The wide applicability of cell therapy has been reviewed throughout literature. This review provides an overview of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…We found that cell therapy proved to generate a robust beneficial effect in animal models of secondary lymphedema. Although several in vitro and in vivo studies have reported beneficial effects of cell therapy against secondary lymphedema [ 21 , 49 , 50 ], a formal meta-analysis that assesses the regenerative activity of cell therapy in animal models of secondary lymphedema had not been performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that cell therapy proved to generate a robust beneficial effect in animal models of secondary lymphedema. Although several in vitro and in vivo studies have reported beneficial effects of cell therapy against secondary lymphedema [ 21 , 49 , 50 ], a formal meta-analysis that assesses the regenerative activity of cell therapy in animal models of secondary lymphedema had not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, cell therapy with differentiated or progenitor cells has emerged as a new research target in the therapy of secondary lymphedema [ 21 , 22 ]. Although the cellular pathways through which stem cell therapy could help lymphedema patients are unclear, in vitro studies indicate that stem cells may differentiate into lymphatic endothelial-like cells under in vitro culture conditions and can improve interstitial fluid drainage when injected in vivo [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies assessing the potential of adipose, mesenchymal, and induced pluripotent stem cells for the treatment of lymphedema have shown promising preclinical and clinical outcomes. The positive effects were mediated by the antiinflammatory, antifibrotic, and antioxidative effects of the stem cells, as well as, most importantly, the regeneration of lymphatic conduits [167]. Secondary lymphedema develops mostly in a delayed fashion, often years after the injury.…”
Section: Box 2 Current Treatment Options For Lymphedemamentioning
confidence: 99%
“…At present, surgery is one of the main approaches for breast cancer treatment [ 5 , 6 , 7 , 8 ]. However, the complications of conventional surgery include lymphedema, fat necrosis, wound infection, range-of-motion restriction, and arm paraesthesia [ 7 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, surgery is one of the main approaches for breast cancer treatment [ 5 , 6 , 7 , 8 ]. However, the complications of conventional surgery include lymphedema, fat necrosis, wound infection, range-of-motion restriction, and arm paraesthesia [ 7 , 9 , 10 , 11 , 12 , 13 , 14 ]. Robot-assisted systems for oncologic surgery are approved by the US Food and Drug Administration (FDA) for specific abdominal surgical interventions.…”
Section: Introductionmentioning
confidence: 99%